The Impact of the US-China Trade War on the Application of Islamic Law in Indonesia - Luhuringbudi, Teguh; Fatahillah, Wilnan; Muhtar, Amin; Masuwd, Mowafg Abrahem; Alrumayh, Safa Husayn (Islamic Law and Social Issues in Society, 2025)
The main issue addressed in this research is the impact of the US-China trade war on the application of Islamic law in Indonesia, particularly from the perspectives of Jināyah, Aḥwāl al-Shakhṣiyyah, and Islamic Economic Law. This study aims to understand how Islamic law can provide a relevant framework for addressing this trade conflict's social and economic challenges. The methods employed include qualitative analysis, with data obtained through literature studies and observations of social phenomena within the community. The research findings indicate that the trade war has triggered an increase in economic crimes and disrupted social family structures, while highlighting the importance of applying Sharia principles to mitigate these negative impacts. The limitations of this study lie in the lack of in-depth quantitative data and the representation of the perspectives of all involved stakeholders. However, this research offers novelty by integrating legal theories of Islam within the context of a dynamic global economy, as well as providing practical, Sharia-based alternative solutions. Further research is recommended to utilize quantitative approaches and surveys to explore broader community perspectives. By involving various societal elements, a more holistic view of the impact of this trade war is expected, leading to more effective and sustainable policy strategies. This study significantly contributes to the development of Islamic law studies by addressing contemporary challenges faced by Indonesian society within a global context.